2019
DOI: 10.1186/s40834-019-0097-x
|View full text |Cite
|
Sign up to set email alerts
|

Infertility knowledge and treatment beliefs among African American women in an urban community

Abstract: Background To assess infertility knowledge and treatment beliefs among African American women in an urban community in Atlanta, Georgia. Methods This was a cross sectional study at a safety net hospital. A convenience sample of a total of 158 women receiving outpatient obstetrical or gynecologic care from March–April 2017 were recruited. Infertility knowledge and treatment beliefs were assessed using a previously applied and field-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…had male respondents as better scorers. [ 4 18 28 ] A study at Ottawa University revealed that female and male respondents both had analogous and lower scores, this finding was similar to the present study as all the groups had statistically nonsignificant difference. [ 29 ]…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…had male respondents as better scorers. [ 4 18 28 ] A study at Ottawa University revealed that female and male respondents both had analogous and lower scores, this finding was similar to the present study as all the groups had statistically nonsignificant difference. [ 29 ]…”
Section: Discussionsupporting
confidence: 88%
“…[ 3 ] A recent tendency among them was observed wherein first-time parenthood was considered in late thirties. [ 4 5 6 7 ] As child conception is deferred for considerable time giving priority to professional goals, it deteriorates the probability of natural conception and subsequently requires specialized treatment to help the couples. [ 3 ] Statistics are available, emphasized the fact that there was downward trend in the total fertility rate, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Ho et al in a study of patients at SFGH found that level of education and socioeconomic status was inversely proportionate to duration of infertility [28]. Recently, Wiltshire et al assessed infertility knowledge and treatment beliefs among African American women from an urban community in Atlanta, Georgia using a field-tested survey from the International Fertility Decision Making Study [29]. In this population, a lower level of infertility knowledge was identified and, similar to our findings, higher level of education correlated with increased knowledge scores [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wiltshire et al assessed infertility knowledge and treatment beliefs among African American women from an urban community in Atlanta, Georgia using a field-tested survey from the International Fertility Decision Making Study [29]. In this population, a lower level of infertility knowledge was identified and, similar to our findings, higher level of education correlated with increased knowledge scores [29]. The data from prior studies of populations with higher socioeconomic status and health literacy identified several factors strongly associated with fertility knowledge including resource level, region of origin, ethnicity, primary language, education level, and parity [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Obama and other famous Black women have described using ART ( Luna, 2018 ). Nonetheless, Black women, who have higher rates of infertility, are less likely to pursue infertility services than white women, and, when they do, the success rates are much lower ( Shapiro et al, 2017 , Wiltshire et al, 2019 ). Typically, differences in success rates are attributed to a combination of genetic factors, environmental issues, socio-economic status and behavioural factors ( Tal and Seifer, 2013 ).…”
Section: Scaling the Crisis Of Reproducing While Blackmentioning
confidence: 99%